Draft Annual Plan 1976-77 Government of Meghalaya - Planning Commission (Planning Commission, 1976)
The following are the main socio-economic focous which have relevance in gard to the formulation of the Stale Plan: The State has a population of 10.2 lakhs according to the census of 1971 which is slighly less than the of Manipur and about double of Nagaland. The percentage of Slate’s tribal populalon is 80.84 per ecru and that of the scheduled t astes is 0'2 per cent. the area of the Sale is approximately 22,500 sq.km. consisting mostly of mountainous crain. the density of population per sq.km. according to 1971 census was 45 having risen from 33 in 1961.
Planning Department Government of Meghalaya